1975
DOI: 10.1084/jem.142.5.1327
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stimulation of human lymphocyte subpopulation.

Abstract: One basic attribute of lymphocytes is their ability to recognize self from nonself. Lymphoblastoid transformation and the associated [3H]thymidine incorporation in in vitro cultures of lymphocytes is generally recognized as a response to nonself antigens . We report here on the surprising finding that in vitro stimulation occurs among autologous lymphocytes in the mixed lymphocyte culture (MLC) test. The most likely explanation of our findings is that among lymphocytes obtained from one sample of peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
105
1
2

Year Published

1978
1978
1990
1990

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(116 citation statements)
references
References 17 publications
8
105
1
2
Order By: Relevance
“…Several years ago, it was discovered that the mixing of autologous T cells with non-T cells resulted in a proliferative response of the T cells in response to stimulation by the non-T cells (1,2). This response was called the autologous mixed lymphocyte reaction (MLR).…”
Section: In Normal Individuals T Cells Are Stimulated To Proliferate mentioning
confidence: 99%
“…Several years ago, it was discovered that the mixing of autologous T cells with non-T cells resulted in a proliferative response of the T cells in response to stimulation by the non-T cells (1,2). This response was called the autologous mixed lymphocyte reaction (MLR).…”
Section: In Normal Individuals T Cells Are Stimulated To Proliferate mentioning
confidence: 99%
“…3, upper) (Fig. 4, lower left) (28,29 1 hr at room temperature with sufficient antisera to human leukocyte type I interferon to neutralize 100 units of antiviral activity. The antiviral activity in supernatants from both T cells and B cells with monocytes was reduced by at least 60% after incubation with antisera to type I interferon (30) indicating that the interferon was Type I rather than immune (Type II).…”
Section: Effect Of Recurrent Infection On Lymphocytementioning
confidence: 99%
“…In the autologous mixed lymphocyte response, it has been reported that T cells proliferate in response to autologous non-T cells (26,27); an inhibitory effect of anti-Ia antibodies on this response has been reported from several laboratories (28)(29)(30). We recently reported (22) 2 that the sera of patients with active SLE contain anti-Ia antibodies of the IgG and IgM class.…”
Section: Antigenic Stimulation Of Normal Subjects With Purified Protementioning
confidence: 99%